Exploring Restrictions to use of community greenways for physical activity through structural equation modeling - Fu, Erkang; Deng, Xiaoyu; Wu, Yuanhao; Li, Lin; Xiong, Yilin; Li, Mengzhou; Zhang, Zihan; Du, Juan; Li, Xinyun; Li, Xi (Frontiers in Public Health, 2023)
Public health problems caused by rapid urbanization have attracted more and more attention. Existing studies show that improving the frequency and duration of physical activity can effectively reduce the disease risk of urban residents. Community greenway, as a green public activity space directly serving community residents, is one of the best spatial carriers to bring health benefits to people. Although the scale and scope of greenway construction have been increasing in recent years, the utilization rate of some greenways is not high due to various reasons, which restricts people to carry out healthy physical activities in greenway space.In this study, the greenway of Nancheng Community in Wenjiang District, Chengdu City, China was selected as the research object, and a structural equation model was constructed to explore the objective environmental factors and individual characteristics of the community greenway's restriction on physical activity of the population.The results show that use experience, greenway landscape, safety and accessibility are important factors that restrict people's willingness to physical activity in community greenway environment. The results of this study provide a thinking direction for improving the willingness of greenway people to physical activity, and further provide a theoretical basis for the healthy design and transformation of community greenway space.